Boosted Cr(VI) clean up over magnetically recoverable NiS/γ-Fe2O3/C type-II heterostructure derived from bimetal (Fe/Ni)-organic framework under visible light. (1st October 2021) - Rashid, M.; Mowla, D.; Esmaeilzadeh, F.; Dashtian, K.; Bahmani, M.
Abstract: Cr(VI), as a toxic species derived from processes such as electroplating, is harmful to humans, plants, animals, and microorganisms. Thus, it is required to remove and recycle Cr(VI) for chromium resource keeping and prevent toxicity issues. Here, a novel magnetically recoverable NiS/γ-Fe2 O3 /C type-II heterojunction was successfully prepared via one-pot calcination of MIL-101(Fe/Ni) nanoflakes as a propitiatory template in the presence of Na2 S precursor. In this calcination process, the Ni/Fe in MIL-101 acts as a metallic source for simultaneous construction of NiS nanoparticles on the γ-Fe2 O3 surface by an in-situ solid-state reaction and organic ligand in MIL-101 acts as an in-situ carbon source to form a C matrix for encapsulation of NiS/γ-Fe2 O3 nanoparticles. NiS/γ-Fe2 O3 /C type-II heterojunction can adequately harvest visible light, boost the interfacial separation and quench the recombination of photogenerated charge transfer agents, proceeding significant photoreduction of Cr(VI). The proposed system exhibits a superior photocatalytic reduction activity of Cr(VI) with an efficiency of 83.85% and a DF value of 0.776 at optimum values of 20 mg/L of Cr(VI), 0.003 g NiS/γ-Fe2 O3 /C type II heterojunction and 35 min irradiation time. A scavenging experiment confirmed that holes and OH radicals could be entirely trapped by tartaric acid and a photocatalytic mechanism based on the other electrochemical, optical, and physicochemical characterizations was proposed. These findings give a new approach and insight to synthesize high-performance type-II heterojunction-based photocatalysts for promising future applications. Graphical abstract: Image 1 Highlights: MOF-derived magnetically recoverable NiS/γ-Fe2 O3 /C type-II heterostructure was synthesized for the first time. NiS/γ-Fe2 O3 /C type-II heterostructure could reduce Cr(VI) under visible-light irradiation. The central composite design was applied to achieve superior photoreduction efficiency. The synergy between electron acceptor-NiS and active γ-Fe2 O3 electron sink-was discussed.